Indoor Navigation Systems Using Annotated Maps in Mobile Augmented Reality - Rehman Ullah, Khan; Yin, Bee Oon; Amalia, Madihie; Chia, Shu En (IJICC, 2019)
A Mobile Augmented Reality indoor navigation framework composed of several modules to reduce human cognitive workload and save time by blending the digital and physical worlds seamlessly through aligning the appropriate 3D path with features in the real world through ground detection. The framework helps in better understanding the surrounding especially unfamiliar buildings such as offices, shopping malls and libraries etc. It determines the users starting location via scanning the reference image which is placed at the entrance. The system was tested at the Centre for Academic Information Services (CAIS), Universiti Malaysia Sarawak (UNIMAS). The results proved that the system provides a good platform to show the location information without requiring hardware installation and a strong wireless connection.